(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
Der vorliegende Beitrag nimmt das Fach GL und die damit verbundenen Chancen und Herausforderungen einer gesellschaftswissenschaftlichen Fächerintegration an den Gesamtschulen in NRW in den Blick. Dafür wurden Professor*innen und Lehrkräfte interviewt. Als Hauptergebnis wurde ein Modell erstellt und ein Handlungsbedarf auf verschiedenen Ebenen erkannt, welcher notwendig erscheint, um den Status quo und die damit verbundenen Herausforderungen zu überwinden und die Potentiale des Faches entfalten zu können. This article focuses on the subject of GL (German: Gesellschaftslehre, rough translation; social sciences; i.e. a school subject that includes geography, history, politics and economics) and the opportunities and challenges of integrating social science subjects in comprehensive schools in the German federal state of North Rhine-Westphalia. University professors and teachers were interviewed for this purpose. The main outcome was the creation of a model which identified a need for action on various levels. This is deemed necessary to overcome the current status quo and its related challenges and to unlock the potential of the subject.